Increasing The Role Of Pregnant Women And Toddler Kader For Early Detection And Prevention Of Stunting Pregnancy To Toddler Period - Lusiana, Deni (Sahabat Publikasi Kuu, 2024)
Posyandu for toddlers and pregnant women is one of the services that has direct contact with the community. Posyandu activities for toddlers and pregnant women focus on preventive efforts including early detection and empowerment to prevent stunting. The implementation of posyandu for toddlers and pregnant women is driven by cadres from the local community who are willing and work voluntarily with the assistance of Health Center health workers. So it is important to carry out cadre training to distribute quality cadres both in number and quality. Training for posyandu cadres for toddlers and pregnant women refers to the curriculum and training modules for posyandu cadres published by the Indonesian Ministry of Health. Stunting prevention can be done by early detection at posyandu for toddlers and pregnant women. The material provided is about early detection of stunting from measurement methods, interpretation and accompanying menus for stunting prevention. The implementation of PkM began with providing material twice and then evaluation once in the RW 05 cadre area. The counseling was attended by 21 cadres of toddlers and pregnant women in the Demangan area from RW 01-12. Cadres are also evaluated pre-post on the level of cadre knowledge regarding the materials provided by the team. The results show that there has been a change or increase in cadres' knowledge regarding early detection of stunting. The things that have been done are important to support the 8000 HPK program to prevent stunting so as to achieve control of the stunting rate due to the role and involvement of posyandu cadres for toddlers and pregnant women.